2008
DOI: 10.1021/ci700415g
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ligand-Based and Receptor-Based Virtual Screening of HIV Entry Inhibitors for the CXCR4 and CCR5 Receptors Using 3D Ligand Shape Matching and Ligand−Receptor Docking

Abstract: HIV infection is initiated by fusion of the virus with the target cell through binding of the viral gp120 protein with the CD4 cell surface receptor protein and the CXCR4 or CCR5 co-receptors. There is currently considerable interest in developing novel ligands that can modulate the conformations of these co-receptors and, hence, ultimately block virus-cell fusion. This article describes a detailed comparison of the performance of receptor-based and ligand-based virtual screening approaches to find CXCR4 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 99 publications
5
96
0
Order By: Relevance
“…To evaluate the hits list and the precision of the applied methods the following metrics were used, typically applied in searches with pharmacophoric models (25). …”
Section: Obtaining and Hits Additionmentioning
confidence: 99%
“…To evaluate the hits list and the precision of the applied methods the following metrics were used, typically applied in searches with pharmacophoric models (25). …”
Section: Obtaining and Hits Additionmentioning
confidence: 99%
“…A similar homology modeling study was also performed to construct homology models of CXCR4 and CCR5. The models were used for virtually screening a library consisting of 602 known CXCR4 and CCR5 inhibitors and some 4,700 similar, presumed inactive, molecules for comparison of ligand-based shape-matching searches and receptor-based docking methods (48). Although these studies described valuable trials in developing CXCR4 antagonists through computational methods, the revealed CXCR4 crystal structures are much different from the structures constructed by homology modeling.…”
Section: Cxcr4mentioning
confidence: 99%
“…In practice, because these rotations are not known a priori, the consensus shape is constructed iteratively as described previously [44]. We have shown that the consensus shapebased representation can be used to capture the essential 3D shape features of several known high-affinity ligands and to encode them in the form of a single representative pseudomolecule which can be used as a VS query [45][46][47][48].…”
Section: Equationmentioning
confidence: 99%